2021
DOI: 10.21608/assjm.2021.192149
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Testicular and Hormonal Serum Profiles of Arabian Stallion during Breeding Season in Algeria

Abstract: Several studies have shown relationship of biometric testicular, hormonal profiles and fertility. Objective of present research were to predict the fertility of stallion by biometric testicular and hormonal analysis. Measurement of the testis of adults Arabian stallions (n=36) from National Haras Chaouchoua of Tiaret, Algeria. The length (TL), the width (TW), the height (TH), and the scrotal width of the testicles (TSW) during three consecutive seasons (April: 2014(April: -2016. From these measurements, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(1 reference statement)
1
1
0
Order By: Relevance
“…This was comparable with previous reports showed that testicular size, and sperm production were significantly affected by season, and the best values were recorded in May, June, or July (Pickett, 2018). We also reported that the testicle biometry as well as the width of total scrotum were higher during summer season compared with other seasons, which is in agreement with previous studies reported that stallions have higher testicular measurements during summer and spring, which subsequently leads to increase sperm production and libido (Hind et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This was comparable with previous reports showed that testicular size, and sperm production were significantly affected by season, and the best values were recorded in May, June, or July (Pickett, 2018). We also reported that the testicle biometry as well as the width of total scrotum were higher during summer season compared with other seasons, which is in agreement with previous studies reported that stallions have higher testicular measurements during summer and spring, which subsequently leads to increase sperm production and libido (Hind et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…The results of measuring the concentrations of hormones in the blood plasma of stallions are shown in Table 2. It is known from the literature that the concentration of testosterone in healthy stallions normally varies from 0.04 to 1.02 ng/ml (Haffner et al 2010;Seale 2010;Hind et al 2021;Basiru et al 2022), while the median estradiol concentration in healthy stallions normally varies from 13.40 -66 pg/ml (Haffner et al 2010;Basiru et al 2022). The normal cortisol concentration in healthy stallions varies from 19.88 -70 ng/ml (Tamanini et al 1983;Villani et al 2006;Haffner et al 2010).…”
Section: Resultsmentioning
confidence: 99%